Effects of Credit Risk Management on Performance of Banks in Kenya - Odawo, George Onyango; Makokha, Elizabeth Nambuswa; Namusonge, Gregory (Archives of Business Research, 2019)
The purpose of study was to analyze the effects of credit risk management on performance of banks in Kenya. The study was guided by the following specific objective; to determine the effects of on bank performance in Kenya. Lending is an investment and therefore as the bank constructs a portfolio it considers an “efficient frontier” of optimal portfolios, offering the maximum possible expected return for a given level of risk. The study was based on modern portfolio, capital asset pricing and liquidity preference theories. It considered the credit scoring model as statistical analysis used by banks to evaluate worthiness of a borrower. The target population of interest was 44 commercial banks categorized into 28 local and 16 foreign banks. They are also categorized into small, medium and large banks. The study used census survey because of the small population. The questionnaires were administered to all respondents of commercial banks in Kenya. Piloting was done to check reliability and validity of data collection and instruments. Data was coded, edited to bring meaning. Multiple regression was also used to test the significance of one variable to the others. Additional secondary data in form of annual reports and financial statements were obtained from Central Bank of Kenya for the period 2011 to 2016. Data collected was analyzed using SPSS version 21.The null hypothesis that liquidity do not have statistically significant influence on of banks performance in Kenya was rejected. Therefore, the independent variable had significant influence on banks performance in Kenya. The bank should take into consideration potential future changes in economic conditions when assessing individual credits and their credit portfolio. The study is significant especially to decision makers involved in the implementation of credit risk management for their banks. The credit managers are able to make strategic, tactical and operational decisions based on the results of a scientific study rather than relying on trial and error.